Negotiating 'outer Europe': the Trades Union Congress (TUC), transnational trade unionism and European integration in the 1950s. Issue 1 (2nd January 2020) - Broad, Matthew
ABSTRACT: The 1950s were a frenetic moment in the European integration process during which the European Economic Community (EEC), the ultimately abortive Free Trade Area (FTA), and subsequently the European Free Trade Association (EFTA) were all negotiated. Trade unions showed keen interest in these schemes; moreover, their own highly institutionalised cooperation suggested they might come to play a key role in shaping them. And yet scholars have argued how divergent traditions and domestic pressures precluded the emergence of a coherent trade union platform on European unity. While not rejecting the structural weaknesses of union internationalism in this regard, this article asks why union centres nevertheless continued to engage with one another on the integration question. Focusing on the British Trade Unions Congress (TUC) and deploying a transnational approach to best understand the interaction between the national and international levels, it shows that union linkages still offered the TUC and its counterparts a valuable chance to learn from and persuade others – and even their governments – of their views, objectives and affairs. Such trade union diplomacy was thus in and of itself valuable despite wider union spats and misgivings, and did at times impact the broader language and approach of the countries involved.